“Another side of the picture”: Analyzing the Outsider’s Perspective in Virginia Woolf’s A Passionate Apprentice - Ammendola, Serena (Margins/Marges/Margini, 2024)
The fact that the diary form includes more genres and mixes the public aspect with the private one has meant that it is considered a "minor" genre compared to the more canonical ones. Over time its alleged lack of rules and its hybrid and elusive nature has led critics to associate the diary with traditional women's literature. Women's diaries are therefore doubly marginal within the literary tradition. This marginality, however, has not prevented the diary from becoming a means of free expression and emancipation of the woman writer. A Passionate Apprentice is the collection of Virginia Stephen's youth diaries from which the author's spontaneous decision to write from the margin emerges. It is a space that Virginia herself shapes and allows her to analyze and challenge social hypocrisy and family pretensions. In an extreme rejection of Victorian society and its masculine tradition, Woolf tries not to succumb to the "cogwheels" of patriarchal power by using the diary as the personal space of an outsider. The choice to write from the margin is conscious though painful, but the author's voice becomes more convinced precisely when ‒ in pursuit of her aesthetic quest ‒ Virginia crosses new boundaries and finds her own vision as a professional writer. The first part of the paper ‒ after a brief introduction to the diary genre ‒ focuses on the 1897 diary and Virginia's creation of the fictional character of Miss Jan. The second part focuses on the 1903 diary and the observations of Victorian society and its mechanisms from a marginal perspective that allows Woolf to grasp deeper meanings.